Smart Greenhouse Multıfactor Monıtorıng Usıng Iot - Modani, Varsha; Patil, Ravindra; Puri, Pooja (International Journal of Engineering and Technology, 2018)
Agriculture plays vital role in the development of agricultural country. Agriculture supports directly or indirectly the economic growth of the country. The biggest thing that holds back the development in the agricultural productivity and efficiency is manual interventions. Agriculture put lots of emphasis on human care in detection and control of different factors such as environment which leads to wastage of manpower and also the desired results are not achieved due to human monitoring error. Greenhouse agriculture in large extent is in urgent need to control the environment factors which give optimum growth of plants. With internet era, proposed work is an integration of greenhouse with IoT. In proposed work Intel Galileo Gen 2 board is used to monitor and control environmental factors for greenhouse like temperature, humidity, soil moisture and light intensity. The user gets updated constantly about the condition of the greenhouse factors using IoT technology. To transmit the data over internet ESP8266Wi-Fi module is used. The experimental results are displayed on ThingSpeak cloud platform. This system avoids the use of dedicated server PC, with the help of internet connectivity user can access the data from anywhere at any time.
Keywords: ESP8266; Greenhouse; Intel Galileo Gen 2; sensors; ThingSpeak IoT cloud platform.